2011
DOI: 10.1159/000331774
|View full text |Cite
|
Sign up to set email alerts
|

First Day of Life Reference Values for Pleth Variability Index in Spontaneously Breathing Term Newborns

Abstract: Background: The perfusion index (PI), derived from the pulse oximetry signal, has been shown to be an accurate predictor for identifying high illness severity in neonates. The plethysmographic variability index (PVI) is a measure of the dynamic change in PI occurring during a complete respiratory cycle. Objectives: The aim of this study was to establish the reference range of PVI in spontaneously breathing term newborns. Methods: PI and PVI values were assessed in 242 term newborns during the first day of life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 34 publications
1
14
2
1
Order By: Relevance
“…PVI thus appeared inversely related to cardiac preload, as already demonstrated in spontaneously breathing healthy adults (26). In healthyterm neonates, an increase in PVI during crying and its positive correlation with heart rate also suggest that this parameter may be an indirect marker of cardiac preload (23).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…PVI thus appeared inversely related to cardiac preload, as already demonstrated in spontaneously breathing healthy adults (26). In healthyterm neonates, an increase in PVI during crying and its positive correlation with heart rate also suggest that this parameter may be an indirect marker of cardiac preload (23).…”
Section: Discussionsupporting
confidence: 68%
“…In paediatrics, two recent studies reported controversial results about the accuracy of dynamic variables derived from the plethysmographic waveform to predict fluid responsiveness for mechanically ventilated patients under general anaesthesia (21,22). In neonatology, a median PVI value of 20 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)% was recently reported in spontaneously breathing-term neonates on the first day of life, mainly influenced by the behavioural status of the newborn (23). Our study is the first to record PVI values in premature neonates during IPPV, but these conditions did not result in major differences regarding the PVI data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Имеются также данные о том, что вариабельность амплитуды пульсовой волны отра-жает преднагрузку у пациентов на спонтанном ды-хании [13,22,36].…”
Section: мониторинг г емодинамики особенности у новорож денныхunclassified